2018
DOI: 10.1051/0004-6361/201629304
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Hi-C EUV brightenings

Abstract: We study the thermal structure and energetics of the point-like EUV brightenings within a system of fan loops observed in the active region AR 11520. These brightenings were simultaneously observed on 2012 July 11 by the HIgh-resolution Coronal (Hi-C) imager and the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO). We identified 27 brightenings by automatically determining intensity enhancements in both Hi-C and AIA 193 Å light curves. The energetics of these brightenings were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…The finding that the conductive losses are much more efficient suggest that there is more energy involved in the events than that being seen as was also suggested by Peter et al (2014). Similar results were obtained for Hi-C EUV bright dots studied by Subramanian et al (2018).…”
Section: Summary and Discussionsupporting
confidence: 87%
“…The finding that the conductive losses are much more efficient suggest that there is more energy involved in the events than that being seen as was also suggested by Peter et al (2014). Similar results were obtained for Hi-C EUV bright dots studied by Subramanian et al (2018).…”
Section: Summary and Discussionsupporting
confidence: 87%
“…Furthermore, the range of computed energies falls within the cluster of values that have been reported in the literature: they are consistent with or smaller than the values reported by 8 × 10 24 −1.6 × 10 26 erg), Berghmans et al 1998; 5 × 10 24 −3 × 10 27 erg), and Winebarger et al (2013; 2.0−6.3 × 10 24 erg). On the other hand, Aschwanden et al (2000), Parnell & Jupp (2000), and Subramanian et al (2018) reported energy ranges (5 × 10 23 −5 × 10 26 erg, 10 23 −10 26 erg, and 0.3−30.0 × 10 24 erg, respectively) whose low-end values are below the lowest energies we detected. Moreover, studies of active region weak transient brightenings report larger energies than ours (e.g., Shimizu 1995; 10 25 −10 29 erg and Hannah et al 2008; 10 26 −10 30 erg).…”
Section: Implications For Chromospheric Heatingcontrasting
confidence: 67%
“…Nanoflares, events with energies less than 10 24 erg, are expected to occur as a result of magnetic reconnection in elemental, tangled magnetic flux tubes that are below the resolution limit of present-day instruments. So far only detections of individual events with energy down to the "high-end" limit of Parker's estimate have been achieved (e.g., Berghmans et al 1998;Parnell & Jupp 2000;Aschwanden et al 2000;Winebarger et al 2013;Régnier et al 2014;Joulin et al 2016;Subramanian et al 2018). It has been argued that these small events could heat the upper atmosphere if the energy released during various types of flarelike activity follows a power-law frequency distribution with energy that has an index α ≥ 2 (e.g., Hudson 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained as follows. During the impulsive phase, conductive losses dominate and radiative losses are negligible (see also Rajhans et al 2021;Subramanian et al 2018;Cargill et al 1995). Therefore, the sum of enthalpy and kinetic energy flux across coronal base γ γ−1 P 0 v 0 + 1 2 µn 0 v 2 0 is approximately equal to the conduction flux (F 0 ) across it.…”
Section: Density Computed By Ebtel2 and Ebtel3mentioning
confidence: 99%